Support based on psychoeducation intervention to address quality of life and care burden among caregivers of patients with cancer: a randomized controlled trial - Mirhosseini, Seyedmohammad; Imani Parsa, Fateme; Moghadam-Roshtkhar, Hasan; Basirinezhad, Mohammad Hasan; Ameri, Malihe; Ebrahimi, Hossein (Frontiers in Psychology, 2025)
IntroductionCancer affects not only patients but also their family caregivers, causing increased caregiving burden and reduced quality of life. The aim of this study was to evaluate the impact of a psychoeducation intervention on improving the quality of life and reducing caregiving burden among caregivers of cancer patients.MethodsThis study employed a non-blinded randomized controlled trial design involving 66 family caregivers of cancer patients undergoing chemotherapy in Shahroud, Iran in 2024. Of the 69 caregivers initially approached, one declined to participate, and two were excluded due to lack of smartphone access, leaving a final sample of 66 caregivers. Participants were assigned to either the psychoeducation intervention program or the control group using the quadruple block randomization method. The intervention spanned 3 months and consisted of six online group sessions lasting 35–45 min each. The psychoeducation intervention was delivered by trained psychiatric nurse. Data were collected before and 1 month after the intervention using the SF-36 quality of life questionnaire and the Novak and Guest care burden inventory. Statistical analysis was conducted using chi squared, independent t-tests, and the linear regression analysis with a significance level set at 0.05.ResultsThe primary outcome of this study was the change in caregivers’ quality of life and caregiver burden. Initially, both groups exhibited similar average scores for care burden and quality of life (p > 0.05). The intervention group showed a significant reduction in caregiving burden by 4.1 ± 13.7, whereas the control group experienced a slight increase of 2.5 ± 12.0. Similarly, quality of life scores improved by 4.7 ± 16.9 in the intervention group but declined by 8.6 ± 15.3 in the control group. Regression analysis indicated that the psychoeducation group demonstrated significantly lower caregiving burden scores and higher quality of life scores following the intervention compared to the control group.ConclusionCaregivers of cancer patients often face significant burdens that impact their quality of life. Psychoeducational interventions focusing on coping, problem-solving, and stress management should be integrated into cancer care plans to provide essential support.Clinical trial registrationhttps://irct.behdasht.gov.ir/trial/54613, identifier IRCT20180728040617N3.